Apakah Magang dan Mata Kuliah Kewirausahaan Mempengaruhi Keputusan Berkarir Mahasiswa? - Maghfiroh, Rahma Ulfa; Tantriana, Deasy; Hamidah, Kuni Auliya; Damayanti, Yosinta; Laily, Zuhrotul (Jurnal Manajemen dan Inovasi (MANOVA), 2023)
The main purpose of this research to get to analysis of internship and entrepeneurship course with organizational experience as moderating variables career decisions in management students at the State Islamic University of Sunan Ampel. This data collection from questionnaires conducted by alumni and students of the Management Study Program of the State Islamic University of Sunan Ampel Surabaya in the 2018 batch. Sampling was using a simple random sampling technique with a total sample of 111 respondents. In this case use partial least square analysis with the result from this data analysis showed that internship variable has a positive and significant effect on the career decision variable, entrepeneurship course variable has no influence on the career decision variable, organizational experince variable is not able to moderate the effect of internship variable on career decision variable, and organizational experience variable is not able moderate the effect of entrepreneurship course variable on career decision.